(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The Paraíba do Sul River (PSR) drainage basin in Southeastern Brazil covers one of the most industrialized and densely populated regions of the country. The impact of chemical contamination on the PSR basin seems to be more pronounced in its middle reach where a number of potentially polluting plants are located. In this study, we used hepatic EROD activity - a biomarker of exposure to CYP1A-inducing pollutants (e.g. PAHs, PCDD/Fs, PCBs) - and the incidence of micronucleated erythrocytes (Mn) in the peripheral blood - a biomarker of effects of DNA-damaging agents (e.g. PAHs) - to evaluate the effects of pollution on two native fish species, Geophagus brasiliensis and Pimelodus maculatus. Results showed that the incidence of Mn and EROD in G. brasiliensis and P. maculatus from the two most downstream sites (Três Rios Town and Piabanha River) were markedly higher than the incidence of Mn and EROD recorded in fish from the most upstream site (Funil Reservoir). Our findings are consistent with the view that CYP1A-inducing activity and increased DNA-damage are found in fish caught in sampling sites located downstream of the stretch where there are several industries that are potential sources of PAHs and CYP1A-inducing contaminants.